2014
DOI: 10.1111/adb.12146
|View full text |Cite
|
Sign up to set email alerts
|

Light alcohol intake during adolescence induces alcohol addiction in a neurodevelopmental model of schizophrenia

Abstract: Schizophrenia is a mental disorder characterized by a series of positive, negative or cognitive symptoms but with also the particularity of exhibiting a high rate of co-morbid use of drugs of abuse. While more than 80% of schizophrenics are smokers, the second most consumed drug is alcohol, with dramatic consequences on frequency and intensity of psychotic episodes and on life expectancy. Here we investigated the impact of light alcohol intake during adolescence on the subsequent occurrence of alcohol addictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 49 publications
(61 reference statements)
4
32
0
1
Order By: Relevance
“…While the hamster serves as a useful bioassay for assessing the effects of antipsychotics on alcohol drinking in patients with SCZ, it is not an animal model of SCZ. Thus, future studies will need to draw upon such an animal model (e.g., the neonatal ventral hippocampal lesioned rat; Jeanblanc et al, 2014), and on techniques such as magnetic resonance spectroscopy and microdialysis to assess neurotransmitter functioning. Both directions of research are required to better understand the mechanism by which CLOZ or CLOZ-like drugs reduce alcohol drinking in animals, in patients with SCZ, and potentially, in those with AUD alone.…”
Section: Discussionmentioning
confidence: 99%
“…While the hamster serves as a useful bioassay for assessing the effects of antipsychotics on alcohol drinking in patients with SCZ, it is not an animal model of SCZ. Thus, future studies will need to draw upon such an animal model (e.g., the neonatal ventral hippocampal lesioned rat; Jeanblanc et al, 2014), and on techniques such as magnetic resonance spectroscopy and microdialysis to assess neurotransmitter functioning. Both directions of research are required to better understand the mechanism by which CLOZ or CLOZ-like drugs reduce alcohol drinking in animals, in patients with SCZ, and potentially, in those with AUD alone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using animal models have also indicated that voluntary ethanol drinking during adolescence can, in some models, be shown to facilitate the acquisition of alcohol self-administration, increase craving behavior, and/or increase the probability of relapse in those animals in adulthood (see Alaux-Cantin et al, 2013; Gilpin, Karanikas & Richardson, 2012; Jeanblanc et al, 2015; McBride et al, 2005; Serlin & Torregrossa, 2015; Spear, 2000a; Toalston et al, 2015). However, other studies have shown that ethanol exposure during adolescence has no effect on subsequent ethanol consumption in adulthood (Slawecki & Betancourt, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Chambers' group has largely investigated the adult consumption of drugs of abuse such as cocaine [77,78], nicotine [79,80], and also alcohol [81,82] with this model showing increased consumption of the different drugs of abuse at adulthood. However, our group was the first to investigate the impact of adolescent alcohol exposure on subsequent AUDs in adulthood in the NVHL model of schizophrenia [83]. In this study, we found that moderate alcohol consumption using a 10 % continuous access two-bottle choice paradigm during adolescence (postnatal days 28 to 42) is necessary to observe at adulthood a loss of control over alcohol consumption.…”
Section: Schizophreniamentioning
confidence: 85%